Corporate governance and intellectual capital: evidence from public and private university / Akma Hidayu Dol @ Abdul Wahid, Nor 'Asyiqin Abu and Wannoraini Abdul Latif - Dol @ Abdul Wahid, Akma Hidayu; Abu, Nor 'Asyiqin; Abdul Latif, Wannoraini (Research Management Institute (RMI), 2012)
This study was conducted to examine the perception of the academicians towards intellectual capital (IC) and governance practice at University A (Public University) and University B (Private University). It also examines the factors to retain the qualified academicians and the relationship between IC and corporate governance (CG) in universities. Analysis reveals that CG is the second factor influences the attraction and retention of the IC. While the foremost factor that attracts academicians to join the universities is the possibility of universities giving opportunity for their academic advancement. Furthermore, the analysis shows that both universities have implemented good governance. However, University A should put more effort in improving its transparency related to accessing the accurate and relevant information, evaluation system, financial allocation and provision for facilities. It also needs to provide more encouragement in academician involvement towards the decision making processes, and thus, giving an opportunity to the academicians to give feedback and suggestion on how to improve the operations within the University. On the other hand, the findings show that University B is lacking in the support of training for career development, rewarding new ideas and outstanding output, creativity and innovation. The academicians in University B also perceived that the University is lack of sufficient support to do a research work and necessary resources to achieve the research target. Finally, statistical result shows a positive relationship between IC and CG. It means, the higher the CG the higher the IC would be retained by the university. This result is further supported by 71.1 percent of the respondents who do not have any intention of leaving the university.